The Woman in the Window : Commerce, Consensual Fantasy, and the Quest for Masculine Virtue in the Russian Novel - Valentino, Russell Scott, 1962- (Book collections on Project MUSE., 2014)
"With chapters on Gogol, Tolstoy, and Dostoevsky as well as Pasternak and Nabokov, The Woman in the Window argues that Russian authors worked through this question via their depictions of "mixed-up men." Such characters, according to Valentino, reveal that in a world where social reality and personal identity depend on consensual fantasies, the old masculine figure loses its grounding and can easily drift away. Valentino charts a range of masculine character types thrown off stride by the new commercially inflected world: those who embrace blind confidence, those who are split with doubt or guilt, and those who look for an ideal of steadfastness and purity to keep afloat--a woman in a window"--Publisher's description